Topographic relationship between maxillary sinus and roots of posterior teeth: a cone beam tomographic analysis - Yildirim, Tuba Talo; Oztekin, Faruk; Tozum, Melek Didem (Istanbul Univ Press, Istanbul Univ Rectorate, 2021)
Purpose The objective of the research was to determine the relationship between root apices and maxillary sinus wall, and to analyze pulpoapical conditions of 2nd premolars, 1st molars, 2nd molars, 3rd molars using cone beam computerized tomography (CBCT). Materials and Methods This study was conducted on a retrospective manner of CBCT images of 1000 maxillary sinus with 500 subjects, who visited the Department of Dento-Maxillofacial Radiology. The association of each teeth with sinus floor and pulpoapical status were categorized. The association among gender, age, lateralization of sinus cavity were evaluated. Results A total of 602 second premolars, 500 first molars, 623 second molars, 347 third molars were evaluated. There were no significant differences between pulpoapical condition of teeth and gender or left and right sides (p=0.065, p=0.072). There were significant associations between pulpoapical condition of all teeth and age (p=0.023), and the relationship of each root with maxillary sinus and age (p=0.037). There was significant association between vertical position and right/left sides in second and third molars (p=0.033). Conclusion Age seems to have relationship with periapical condition of teeth, and the association of root with the sinus cavity.
Keywords: Radiology; Age; Inflammation; Pulp; Root canal